Circulating free T3 associates longitudinally with cardio-metabolic risk factors in euthyroid children with higher TSH - Carreras-Badosa, Gemma; Puerto-Carranza, Elsa; Mas-Parés, Berta; Gómez-Vilarrubla, Ariadna; Cebrià-Fondevila, Helena; Díaz-Roldán, Ferran; Riera-Pérez, Elena; de Zegher, Francis; Ibañez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Frontiers in Endocrinology, 2023)
Introduction Thyroid hormones play major roles in the regulation of body composition and metabolism, and therefore, the relationship between thyroid hormones and cardio-metabolic risk has been extensively studied in adults. In this study, we aimed to test whether free triiodothyronine (fT3) associates longitudinally with cardio-metabolic risk factors in euthyroid children. Methods A prospective study cohort of 599 apparently healthy school-age children were assessed at baseline (mean age 8.1 ± 2.1 years), of whom 270 children were also assessed at follow-up (4 years later). Circulating thyroid-stimulating hormone (TSH), free thyroxine (fT4), and fT3 were measured, and cardio-metabolic risk was assessed by means of body mass index (BMI), waist circumference, visceral fat (by ultrasound), blood pressure, circulating lipids, and homeostasis model assessment of insulin resistance (HOMA-IR) index, both at baseline and at follow-up. Results All studied children had normal thyroid function tests. Independent associations between baseline fT3 and both baseline and follow-up BMI, systolic blood pressure, mean arterial blood pressure, triglycerides, and HOMA-IR were found using multivariate regression analysis (adjusting for sex and baseline age and BMI). Analyses of effect sizes showed that for each 1 unit-increase in baseline fT3 (pg/ml), follow-up BMI–standard deviation score (SDS) increased by 0.31 units (z-score) and systolic blood pressure by 6.6 units (mmHg). The observed longitudinal associations were more robust in children belonging to the upper TSH tertile who showed higher TSH levels and were characterized by weighing more and having the highest fT3 levels. In these children, for each 1 unit-increase in baseline fT3 (pg/ml), follow-up BMI-SDS increased by 0.67 units (z-score) and systolic blood pressure by 10.2 units (mmHg). Conclusions Circulating fT3 associates longitudinally with cardio-metabolic risk factors in euthyroid children with higher TSH. The observed associations of thyroid hormones in these children could conceivably respond to a homeostatic attempt to reduce their cardio-metabolic risk.